(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article has written about the importance of intercultural competence and offers about professional basis of knowledge. Such examples can help to develop not only intercultural communication but also to the professional qualification, understand and solve the problems, in another way, other cultures; to improve cultural aspects of the professional participation; to lead constructional dialogues of foreign people culture, openly to interchange ideas and opinions, again to examine own aims, in the intercultural process like our we learn other cultures . Aim of the article is to improve intercultural communication in the process of learning foreign languages. We can find a lot researchers, for example E.Holl and I.Haleeva’s.